Cold sweat : my father James Brown and me - Brown, Yamma; Fisher, Robin Gaby (Chicago Review Press, 2014)
"Being the child of a global superstar is never easy, but being the daughter of the "Hardest Working Man in Show Business"--that's a category unto itself. Like every little girl, Yamma Brown wanted her father's attention, but fame, drugs, jail, and the complicated women in James Brown's life set the stage for an uncommon childhood. She got caught in the same trap as her mother, doing things in her adult life and troubled marriage that, as a child, she'd promised herself she'd never do. The struggles she went through, both as a child and as an adult, make for a gripping read and, in the end, a profound examination of the nature of celebrity, violence, and survival. Though packed with celebrity appearances ranging from Michael Jackson to Al Sharpton, Cold Sweat ultimately focuses on an everyday issue faced by millions of women--domestic violence--and in this book Yamma faces it in an honest and powerfully moving way"--